P785 The prevalence of inflammatory bowel disease doubled in the last decade in Israel: an epiIIRN national population-based study. (25th January 2019) - Friedman, M; Navon, D; Asayag, N; Focht, G; Brufman, I; Feldman, B; Cahan, A; Ledderman, N; Matz, E; Chowers, Y; Eliakim, R; Ben-Horin, S; et al.
Abstract: Background: Although inflammatory disease (IBD) prevalence is particularly high in Jews, the epidemiology of the disease in Israel is largely unknown. Following the validation of case-ascertainment algorithms for the epiIIRN registry, we retrieved IBD cases from all four Israeli HMOs' databases to calculate national epidemiology trends of IBD in Israel. Methods: Basic demographics of IBD cases identified for the time period 1 January 2003–31 January 2017 were retrieved. Date of diagnosis and IBD type (Crohn's disease (CD) vs. ulcerative colitis (UC)) were determined by previously validated algorithms. Age- and sex-standardised rates were derived from the Israeli Central Bureau of Statistics; time trends were calculated by Kendall's Tau-b statistic. Results: As of January 2017, a total of 42, 022 IBD patients were residing in Israel (prevalence 0.5%), of whom, 37770 (90%) were Jews, 3085 (7%) Arabs, and 1169 (3%) unknown. Of the 42022 patients, 0.11% were 0–5 years of age, 0.26% were 6–9 years, 2.4% were 10–16 years, 38% were 17–39 years, 55% were 40–79 years and the others were >80 years. Since 2003, the Jewish prevalence doubled (0.31 to 0.59%) and the Arab prevalence increased threefold (0.06% to 0.17%). During 2006–2016, 19378 patients were newly diagnosed with IBD, of whom 23 (0.11%) were diagnosed at the age of 0–1 years, 122 (0.63%) at 2–5 years, 280 (1.4%) at 6–9 years, 1907 (9.8%) at 10–16 years, 9820 (50.7%) at 17–39 years and 7226 (37.3%) ≥40 years. Adjusted prevalence of CD and UC per 100000 were 313 and 271 among Jews, and 79 and 94 among Arabs, respectively, indicating that UC predominates only in the Arab population (Graph 1). Israeli IBD prevalence trends. While males slightly predominated in the entire cohort (50.4% vs. 49.6%; p = 0.02), there were more females in the Jewish UC population (51.5% vs. 48.5%, p < 0.001); CD patients were more likely to be males in both Jews and Arabs (51.8% vs. 48.4% in the combined population; p < 0.001). IBD incidence was 18.2/100000 in 2016, and that did not change significantly since 2006. However, UC has decreased from 10.7/100, 000 in 2006 to 7.5/100000 in 2016 ( p = 0.003). On the other hand, there was a significant increase of incidence in children 10–16 years both in CD (from 12.0/100000 to 14.2/100000, p = 0.028) and UC (from 3.9/100000 to 7.2/100000, p = 0.001). Conclusions: IBD prevalence in Israel continues to increase, as does IBD incidence in children, and now affects 0.5% of the population. This study was supported by a grant from the Leona M. and Harry B. Helmsley Charitable Trust.